PERBEDAAN KINERJA KEUANGAN BANK OCBC NISP SEBELUM DAN SESUDAH MERGER DI INDONESIA - Usmany, Lisa Rachel; Badjra, Ida Bagus (E-Jurnal Manajemen; Vol 8 No 8 (2019)DO - 10.24843/EJMUNUD.2019.v08.i08.p12, 2019)
Merger is a merger of two companies into one. Merger decisions have a major influence in improving conditions and improving company employment, because with the joining of two or more companies can support each other's business activities, so that the resulting profits are also greater than if done individually. The purpose of this study is to analyze whether the merger decision can improve Bank OCBC NISP's financial performance and to analyze whether there are significant differences in Bank OCBC NISP's financial performance before and after the merger. This research was conducted at Bank OCBC NISP for a period of 5 years before the merger of 2006-2010 and 5 years after the 2012-2016 merger. Data collection uses the census method, namely through bank OCBC NISP financial statements per year. The data analysis technique used is paried samples t-test. Based on the results of the analysis it was found that the financial performance of CAR, NPL, ROA and LDR had performance improvements and there were significant differences before and after the merger. Keywords : CAR, NPL, ROA, LDR, merger